2016
DOI: 10.1142/s2010135x16500302
|View full text |Cite
|
Sign up to set email alerts
|

Morphology-dependent space charge polarization and dielectric relaxation of CdO nanomorphotypes

Abstract: A versatile approach signifying the morphology-dependent dielectric polarization and relaxation mechanisms of cadmium oxide (CdO) nanosphere, nanoflakes and nanoparallelepiped morphotypes as a function of frequency and temperature is presented. Variation of dielectric property is observed due to the changes of space charge/interfacial polarization resulting from the variations of surface to volume ratio of nanomorphology. Accordingly, colossal dielectric constant value has been observed in CdO nanosphere havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…As demonstrated in Figure 7 f, these photo generated electrons get quickly captured by the α-Fe 2 O 3 nanoparticles, embedded in the negative tribo-layer, that is recognized for its surpassing charge trapping property [ 39 ], confirmed by the appreciable enhancement in the dielectric properties of the PDMS based-composite owing to the insertion of α-Fe 2 O 3 nanoparticles into the pure PDMS ( Figure 7 h), while the generated holes then tend to get neutralized by the recombination with adsorbing negatively charged particles or ions from air [ 40 ]. Considering comparatively lower dielectric constant of the as prepared PDMS film ( Figure 7 h), as the general distinction of dielectric property is noticed because of the changes of space charge/interfacial polarization developing from differences in the surface to volume ratio of the presented structure morphology [ 20 , 41 , 42 , 43 ]. Hence, these trapped electrons successively, are amplified to the previously-available negative tribo-charges, resulting in an enhancement in the surface charge density of PDMS/α-Fe 2 O 3 nanocomposite film, thereby amplifying the output performance of this TENGs upon light illumination.…”
Section: Resultsmentioning
confidence: 99%
“…As demonstrated in Figure 7 f, these photo generated electrons get quickly captured by the α-Fe 2 O 3 nanoparticles, embedded in the negative tribo-layer, that is recognized for its surpassing charge trapping property [ 39 ], confirmed by the appreciable enhancement in the dielectric properties of the PDMS based-composite owing to the insertion of α-Fe 2 O 3 nanoparticles into the pure PDMS ( Figure 7 h), while the generated holes then tend to get neutralized by the recombination with adsorbing negatively charged particles or ions from air [ 40 ]. Considering comparatively lower dielectric constant of the as prepared PDMS film ( Figure 7 h), as the general distinction of dielectric property is noticed because of the changes of space charge/interfacial polarization developing from differences in the surface to volume ratio of the presented structure morphology [ 20 , 41 , 42 , 43 ]. Hence, these trapped electrons successively, are amplified to the previously-available negative tribo-charges, resulting in an enhancement in the surface charge density of PDMS/α-Fe 2 O 3 nanocomposite film, thereby amplifying the output performance of this TENGs upon light illumination.…”
Section: Resultsmentioning
confidence: 99%
“…The dielectric measurements are used to analyze relaxation and conductivity process in materials. The parameters such as particle size, large surface to volume ratio, defects, temperature, doping and plays a vital role in dielectric property in nanoparticles [27][28][29]. Zhao et al results observed that the increase in doping amount of lanthanum oxide with BaSrTiO3 ceramics increases the dielectric constant [30].…”
Section: Introductionmentioning
confidence: 99%
“…Different techniques have been proposed to synthesize CdO films such as spray pyrolysis, 13 sol-gel, 12,14 electrochemical deposition, 11,15 templateengaged approach, 16 chemical bath deposition, 17,18 and solvothermal synthesis. 19,20 To improve its PEC performance and photocatalytic activity, various micro-/nano-nanostructured CdO films have been fabricated. Those structures include nanofibers, 14 nanoboxes, 16 nanowires, 17 nanorods, 1,19 nanoflakes 20 and nanoparticles.…”
mentioning
confidence: 99%
“…19,20 To improve its PEC performance and photocatalytic activity, various micro-/nano-nanostructured CdO films have been fabricated. Those structures include nanofibers, 14 nanoboxes, 16 nanowires, 17 nanorods, 1,19 nanoflakes 20 and nanoparticles. 21 CdS is also an n-type semiconductor and has a suitable bandgap (2.4 eV) for visible light absorption.…”
mentioning
confidence: 99%